School and family relationship: strategy in drug prevention (Research, Society and Development, 2020)
This article addresses the problem of drug use by students at a public school and the preventive actions taken by the school community to minimize this problem. The study had as a locus, a Full-time High School, located in the district of Mangabeira, municipality of Eusébio - Ceará. It aimed to identify the factors that lead young people to use drugs, in order to develop a diagnosis that points out the panorama of drug use at school, the risk and protection factors involved. For data collection, semi-structured questionnaires related to the theme of drugs were used during the 2019 academic period. The analysis of statistical data was performed using the GraphPad Prism 6 software. The level of significance was set at p